The impact of social media influencers on consumer decision-making in the GCC: A theoretical and empirical analysis - Alshihre, Fawaz Mohammed A (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of social media influencers on consumer decision-making in the Gulf Cooperation Council (GCC) region, where social media usage rates are among the highest globally. The purpose of the research is to explore the psychological and social mechanisms through which influencer marketing shapes purchasing behavior. A quantitative research design was employed, drawing on Cognitive Dissonance Theory, Social Identity Theory, and the Elaboration Likelihood Model. Data were collected from 500 respondents across Saudi Arabia, the United Arab Emirates, Qatar, and Kuwait using a structured questionnaire. Regression analysis revealed that identification with influencers is the most influential predictor of consumer decisions, while credibility and value misalignment trigger cognitive dissonance, reducing trust. Peripheral cues, such as emotional and visual content, also significantly affect decision-making. The study concludes that influencer marketing in the GCC is most effective when it aligns with cultural values and fosters emotional and social connections. Practically, brands targeting GCC consumers should prioritize value congruence and community-oriented content strategies to drive consumer engagement and loyalty.